Thermoplastic vulcanized rubber material and preparation method thereof

By using a combination of components such as polyolefin elastomer and styrene block copolymer in thermoplastic elastomer materials, combined with dynamic vulcanization and extrusion processing, the performance balance of existing materials in terms of tensile strength and wear resistance is solved. A thermoplastic vulcanized glue material with excellent wear resistance and mechanical strength was prepared.

CN119119624APending Publication Date: 2024-12-13CHINA ENERGY INVESTMENT CORP LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310695206.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-13
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing thermoplastic elastomer materials have insufficient performance balance in terms of tensile strength and wear resistance, and have failed to effectively take into account both.

Method used

Using thermoplastic vulcanized glue material composed of polyolefin elastomer, styrene block copolymer, crosslinking agent, crosslinking additive and antioxidant, dynamic vulcanization and extrusion process is carried out through a twin-screw extruder to prepare excellent Materials with wear resistance and mechanical strength.

Benefits of technology

The thermoplastic vulcanized adhesive material has achieved a good balance between wear resistance and mechanical properties, and has high tensile strength and excellent wear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004281464460000061
    Figure BDA0004281464460000061
  • Figure BDA0004281464460000071
    Figure BDA0004281464460000071
Patent Text Reader

Abstract

The invention provides a thermoplastic vulcanized rubber material, a preparation method thereof and a product prepared from the thermoplastic vulcanized rubber material. The thermoplastic vulcanized rubber material is obtained by reaction of a composition comprising the following components: 50-80 parts by weight of a polyolefin elastomer, 20-50 parts by weight of a styrene block copolymer, 0.1-1 part by weight of a cross-linking agent, 0.1-1 part by weight of a cross-linking auxiliary agent and 0.01-1 part by weight of an antioxidant, and the sum of the weight of the polyolefin elastomer and the weight of the styrene block copolymer is 100 parts by weight. The thermoplastic vulcanized rubber composition provided by the invention has excellent wear resistance and excellent mechanical strength, and the balance between the wear resistance and the mechanical property is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of elastomers, and in particular, relates to a thermoplastic elastomer vulcanized rubber material and a preparation method thereof. Background Art

[0002] Thermoplastic elastomer materials are a type of polymer material with a special elastic and plastic structure. They have good plasticity and elastic memory and can be processed and shaped within a certain temperature range. Common thermoplastic elastomer materials include polyurethane elastomers, thermoplastic elastomer blends, thermoplastic rubber, etc. These materials are widely used in the fields of automobiles, electronics, medical devices, toys, etc. For example, polyurethane elastomers can be used in car seats, gaskets, sound insulation materials, etc.; thermoplastic rubber can be used in seals, springs, cable connectors, etc.

[0003] CN 108841073B discloses a flame retardant dynamically vulcanized PP / POE elastomer and a preparation method thereof. The elastomer raw materials are as follows: polypropylene, ethylene-octene copolymer, vulcanizing agent, co-vulcanizing agent, antioxidant, activator, softener, anti-dripping agent, compound flame retardant, etc. After the invention introduces the disulfide into the PP / POE elastomer dynamic vulcanization system, the flame retardant effect of the flame retardant system is improved while the mechanical properties and flow properties of the material are enhanced, thereby obtaining a thermoplastic elastomer with good flame retardant effect and excellent mechanical properties.

[0004] CN101845193A discloses a dynamically vulcanized styrene thermoplastic elastomer and a preparation method thereof. The raw materials of the elastomer are as follows: styrene block copolymer, polyolefin, rubber processing oil, inorganic filler, antioxidant, crosslinking agent, and auxiliary crosslinking agent. After the above materials are subjected to dynamic vulcanization extrusion processing, the obtained elastomer has excellent comprehensive performance and basically no odor residue.

[0005] CN 112795127A discloses a polymorphic elastomer and a production method thereof. The materials include thermoplastic elastomer, polyolefin elastomer, softening oil and functional additives. The materials are processed by extrusion to prepare a novel elastomer, and the obtained elastomer has a high elastic recovery rate and excellent mechanical properties.

[0006] CN 108841073B discloses a flame retardant dynamically vulcanized PP / POE elastomer and a preparation method thereof. The obtained material has good flame retardancy and mechanical properties, but the wear resistance and tensile strength of the product are not tested.

[0007] CN101845193A discloses a dynamically vulcanized styrene thermoplastic elastomer and a preparation method thereof. The obtained material has excellent tensile strength, but the tensile strength of the material is low, and the wear resistance of the material is not tested.

[0008] CN 112795127A discloses a polymorphic elastomer and a production method thereof. The obtained material has good tensile strength, and the wear resistance of the material is not tested. The dynamic vulcanization preparation method is not adopted, and the heat resistance is poor.

[0009] Thermoplastic elastomer materials in the prior art still have some deficiencies in terms of performance balance. Therefore, there is a need for a thermoplastic elastomer material with a good balance between tensile strength and wear resistance. Summary of the invention

[0010] In view of the problems existing in the prior art, the present invention provides a thermoplastic vulcanizate material and a preparation method thereof. The thermoplastic vulcanizate material has excellent wear resistance and excellent mechanical strength.

[0011] According to a first aspect of the present invention, there is provided a thermoplastic vulcanizate material obtained by reacting a composition comprising the following components:

[0012] 50 to 80 parts by weight, preferably 50 to 70 parts by weight of a polyolefin elastomer;

[0013] 20 to 50 parts by weight, preferably 30 to 50 parts by weight of a styrene block copolymer;

[0014] 0.1 to 1 parts by weight of a cross-linking agent;

[0015] 0.1 to 1 parts by weight of a cross-linking aid; and

[0016] 0.01 to 1 parts by weight of an antioxidant,

[0017] The total weight of the polyolefin elastomer and the styrene block copolymer is 100 parts by weight.

[0018] Preferably, the thermoplastic vulcanizate material does not contain any softener, for example, the softener may be white oil, paraffin oil and / or naphthenic oil.

[0019] Preferably, the melt flow rate (190°C, 2.16kg) of the polyolefin elastomer is 0.1-2.5g / 10min; more preferably, the melt flow rate (190°C, 2.16kg) is 0.3-2.0g / 10min; more preferably, the melt flow rate (190°C, 2.16kg) of the polyolefin elastomer is 0.3-0.7g / 10min.

[0020] Preferably, the polyolefin elastomer is at least one selected from ethylene-propylene copolymer (EPDM), ethylene-octene copolymer (POE) and ethylene-octene block copolymer (OBC).

[0021] Preferably, the weight average molecular weight of the styrene block copolymer is 50,000 to 300,000, preferably 50,000 to 100,000; the content of styrene is 20wt% to 50wt%, preferably 25wt% to 40wt%.

[0022] Preferably, the styrene block copolymer is at least one selected from styrene / ethylene-butylene / styrene block copolymer (SEBS) and styrene / butadiene / styrene block copolymer (SBS).

[0023] Preferably, the crosslinking agent is at least one selected from di-tert-butyl peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxide)hexane, 1,4-di-tert-butylperoxyisopropylbenzene and diisopropylbenzene peroxide.

[0024] Preferably, the crosslinking aid is at least one selected from triallyl isocyanurate, trimethylolpropane triacrylate and trimethylolpropane trimethacrylate.

[0025] Preferably, the antioxidant is at least one selected from hindered phenol antioxidants, phosphite antioxidants and thioester antioxidants, preferably hindered phenol antioxidants and phosphite antioxidants; more preferably, the antioxidant is at least one selected from antioxidant 1010, antioxidant 245, antioxidant 168 and antioxidant 626.

[0026] Preferably, the thermoplastic vulcanizate material according to the present invention is molded into a 8 mm thick plate by a tablet press and cut into a cylinder with a diameter of 16 mm, and then the wear amount measured by a roller abrasion machine according to the GB / T 9867-2008 method is 170 mm 3 the following.

[0027] Preferably, the thermoplastic vulcanizate material according to the present invention is pressed into a 2 mm thick sheet by a sheet press and cut into standard tensile specimens, and then placed in a test room for 24 hours, and tested using an Instron 5965 testing machine according to the GB / T 528-2009 method to obtain a tensile strength of 18 MPa or more; and a 300% elongation strength of 5.7 MPa or more.

[0028] According to a second aspect of the present invention, there is provided a method for preparing a thermoplastic vulcanizate composition, comprising the following steps:

[0029] (1) blending a styrene block copolymer, a polyolefin elastomer and an antioxidant, and then melt-blending and extruding the mixture through a twin-screw extruder, and granulating the mixture to obtain a primary thermoplastic elastomer material;

[0030] (2) The primary thermoplastic elastomer, the crosslinking agent, the crosslinking aid and other materials are blended, and then dynamically vulcanized and extruded through a twin-screw extruder to obtain a thermoplastic vulcanizate material.

[0031] Preferably, the conditions for melt blending in step (1) are: extrusion temperature of 180-220° C.; extruder speed of 200-300 r / min.

[0032] Preferably, the conditions for melt blending in step (2) are: extrusion temperature of 180 to 220° C.; and extruder speed of 60 to 150 r / min.

[0033] According to a third aspect of the present invention, there is provided a product, which is prepared from the thermoplastic vulcanizate composition according to the present invention.

[0034] The thermoplastic vulcanizate composition according to the present invention has excellent wear resistance and excellent mechanical strength, and achieves a balance between wear resistance and mechanical properties. DETAILED DESCRIPTION

[0035] The testing methods of the relevant performance parameters involved in the following embodiments and comparative examples are as follows:

[0036] 1. Tensile modulus test method

[0037] The weighed composite pellets were pressed into 2 mm thick sheets using a tablet press and cut into standard tensile specimens. After being placed in a test room for 24 hours, the sheets were tested using an Instron 5965 testing machine according to the GB T528-2009 method.

[0038] 2. Determination of wear

[0039] An appropriate amount of the above thermoplastic vulcanizate material was weighed, molded into a plate with a thickness of 8 mm and cut into a cylinder with a diameter of 16 mm, and then measured using a drum abrasion machine according to the GBT 9867-2008 method.

[0040] The present invention will be described in detail below by way of examples. In the following examples,

[0041] Ethylene-octene copolymer (POE), Dow Chemical, brand 8150, melt flow rate 0.5 g / 10 min (190 ° C, 2.16 kg), Mooney viscosity (ML1+4@121 ° C) 33, density 0.868 g / cm 3 ;

[0042] Ethylene-propylene copolymer (EPDM), Dow Chemical, brand 4770P, Mooney viscosity (ML1+4@125℃) is 70, density is 0.87g / cm 3 , the melt flow rate is the melt flow rate is 2g / 10min (190℃, 2.16kg);

[0043] Ethylene-octene block copolymer (OBC), Dow Chemical, brand 9077, density 0.869 g / cm 3 , melt flow rate is 0.5g / 10min (190℃, 2.16kg);

[0044] Styrene block copolymer (SEBS), Sinopec Baling, brand name YH501T, weight average molecular weight 70,000, styrene content 30wt%;

[0045] Styrene / butadiene / styrene block copolymer (SBS), Baling Petrochemical, brand name YH-792, weight average molecular weight of 100,000, styrene content of 40wt%;

[0046] 1,4-di-tert-butylperoxyisopropylbenzene (BIBP) was purchased from Shanghai Dunmei New Material Technology Co., Ltd.;

[0047] Triallyl isocyanurate (TAIC) was purchased from Shanghai Dunmei New Material Technology Co., Ltd.;

[0048] Antioxidant A was antioxidant 168, purchased from Qingdao Jiedejia New Material Technology Co., Ltd.;

[0049] Antioxidant B was antioxidant 1010, purchased from Qingdao Jiedejia New Material Technology Co., Ltd.;

[0050] The raw materials used in the examples and comparative examples are all commercially available.

[0051] Example 1

[0052] 1) 6 kg POE, 4 kg styrene block copolymer (SEBS), 0.01 kg antioxidant A (antioxidant 168) and 0.01 kg antioxidant B (antioxidant 1010) were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded into granules by a twin-screw extruder to obtain TPE. The twin-screw extruder has a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C;

[0053] 2) 10 kg of TPE obtained in step 1, 0.01 kg of 1,4-di-tert-butyl peroxyisopropylbenzene (BIBP) and 0.03 kg of triallyl isocyanurate (TAIC) were stirred for 3 minutes by a high-speed stirrer, and then melt blended and extruded into granules by a twin-screw extruder to obtain TPV. The twin-screw extruder has a screw aspect ratio of 26 / 1, a screw speed of 100 rpm, and a screw extrusion blending temperature of 200°C.

[0054] Example 2

[0055] 1) 6kg POE, 4kg SEBS, 0.01kg antioxidant A and 0.01kg antioxidant B were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded into granules to obtain TPE. The twin-screw extruder had a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 180°C;

[0056] 2) 10 kg of the TPE obtained in step 1, 0.02 kg of BIBP and 0.05 kg of TAIC were stirred for 3 minutes in a high-speed stirrer, and then melt-blended and extruded into granules by a twin-screw extruder to obtain TPV. The twin-screw extruder had a screw aspect ratio of 26 / 1, a screw speed of 100 rpm, and a screw extrusion and blending temperature of 180°C.

[0057] Example 3

[0058] 1) 6kg POE, 4kg SBS, 0.01kg antioxidant A and 0.01kg antioxidant B were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded into granules to obtain TPE. The twin-screw extruder had a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 190°C;

[0059] 2) 10 kg of the TPE obtained in step 1, 0.05 kg of BIBP and 0.1 kg of TAIC were stirred in a high-speed stirrer for 3 minutes, and then melt-blended and extruded into granules by a twin-screw extruder to obtain TPV. The twin-screw extruder had a screw aspect ratio of 26 / 1, a screw speed of 100 rpm, and a screw extrusion and blending temperature of 190°C.

[0060] Example 4

[0061] 1) 7kg EPDM, 3kg SBS, 0.01kg antioxidant A and 0.01kg antioxidant B were stirred for 3 minutes in a high-speed mixer, and then melt blended and extruded into granules to obtain TPE through a twin-screw extruder. The twin-screw extruder has a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 210°C;

[0062] 2) 10 kg of the TPE obtained in step 1, 0.1 kg of BIBP and 0.05 kg of TAIC were stirred for 3 minutes in a high-speed stirrer, and then melt-blended and extruded into granules by a twin-screw extruder to obtain TPV. The twin-screw extruder had a screw aspect ratio of 26 / 1, a screw speed of 100 rpm, and a screw extrusion and blending temperature of 210°C.

[0063] Example 5

[0064] 1) 5 kg of OBC, 5 kg of SEBS, 0.01 kg of antioxidant A and 0.01 kg of antioxidant B were stirred for 3 minutes in a high-speed stirrer, and then melt-blended and extruded into granules by a twin-screw extruder to obtain TPE. The twin-screw extruder has a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion and blending temperature of 200°C;

[0065] 2) 10 kg of the TPE obtained in step 1, 0.02 kg of BIBP and 0.05 kg of TAIC were stirred for 3 minutes in a high-speed stirrer, and then melt-blended and extruded into granules by a twin-screw extruder to obtain TPV. The twin-screw extruder had a screw aspect ratio of 26 / 1, a screw speed of 100 rpm, and a screw extrusion and blending temperature of 200°C.

[0066] An appropriate amount of the POE / SEBS vulcanized rubber material prepared in Examples 1 to 5 was weighed, and tensile specimens were prepared by a tablet press, and the tensile strength and 300% modulus of elongation were tested.

[0067] An appropriate amount of the thermoplastic vulcanizate material prepared in Examples 1 to 5 was weighed, molded into a plate of 8 mm, and the wear amount of the material was tested using a drum abrasion machine.

[0068] The measurement results are shown in Table 1.

[0069] Table 1: Properties of thermoplastic elastomer materials prepared according to Examples 1 to 5

[0070]

[0071] Comparative Example 1

[0072] 1) 6kg POE, 4kg SEBS, 0.01kg antioxidant A and 0.01kg antioxidant B were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded into granules by a twin-screw extruder to obtain TPE. The twin-screw extruder had a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C.

[0073] Comparative Example 2

[0074] 1) 6kg POE, 4kg SEBS, 0.01kg antioxidant A and 0.01kg antioxidant B were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded into granules to obtain TPE. The twin-screw extruder had a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C;

[0075] 2) 10 kg of the TPE obtained in step 1, 0.15 kg of BIBP and 0.2 kg of TAIC were stirred for 3 minutes in a high-speed stirrer, and then melt-blended and extruded into granules by a twin-screw extruder to obtain TPV. The twin-screw extruder had a screw aspect ratio of 26 / 1, a screw speed of 100 rpm, and a screw extrusion and blending temperature of 200°C.

[0076] Comparative Example 3

[0077] 1) 6kg POE, 4kg SEBS, 0.01kg antioxidant A and 0.01kg antioxidant B were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded into granules to obtain TPE. The twin-screw extruder had a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C;

[0078] 2) 10 kg of the TPE obtained in step 1 and 0.02 kg of BIBP were stirred for 3 minutes in a high-speed stirrer, and then melt-blended and extruded into granules by a twin-screw extruder to obtain TPV. The twin-screw extruder had a screw length-to-diameter ratio of 26 / 1, a screw speed of 100 rpm, and a screw extrusion and blending temperature of 200°C.

[0079] Comparative Example 4

[0080] 1) 6kg POE, 4kg SEBS, 0.01kg antioxidant A and 0.01kg antioxidant B were stirred for 3 minutes in a high-speed stirrer, and then melt blended and extruded into granules to obtain TPE. The twin-screw extruder had a screw length-to-diameter ratio of 26 / 1, a screw speed of 250 rpm, and a screw extrusion blending temperature of 200°C;

[0081] 2) 10 kg of the TPE obtained in step 1 and 0.05 kg of TAIC were stirred for 3 minutes in a high-speed stirrer, and then melt-blended and extruded into granules by a twin-screw extruder to obtain TPV. The twin-screw extruder had a screw aspect ratio of 26 / 1, a screw speed of 100 rpm, and a screw extrusion and blending temperature of 200°C.

[0082] Table 2: Properties of elastomeric materials prepared according to Comparative Examples 1 to 4

[0083]

[0084] Obviously, the above embodiments of the present invention are merely examples for clearly explaining the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are within the spirit scope of the present invention.

Claims

1. A thermoplastic vulcanizate material, which is obtained by reacting a composition comprising the following ingredients: 50 to 80 parts by weight, preferably 50 to 70 parts by weight of a polyolefin elastomer; 20 to 50 parts by weight, preferably 30 to 50 parts by weight of a styrene block copolymer; 0.1 to 1 parts by weight of a cross-linking agent; 0.1 to 1 parts by weight of a cross-linking aid; and 0.01 to 1 parts by weight of an antioxidant, Wherein, the sum of the weights of the polyolefin elastomer and the styrene block copolymer is 100 parts by weight.

2. The thermoplastic vulcanizate material according to claim 2, wherein: The melt flow rate (190° C., 2.16 kg) of the polyolefin elastomer is 0.1 to 2.5 g / 10 min; preferably, the melt flow rate (190° C., 2.16 kg) is 0.3 to 2.0 g / 10 min.

3. The thermoplastic vulcanizate material according to claim 1 or 2, wherein: The polyolefin elastomer is at least one selected from ethylene-propylene copolymer (EPDM), ethylene-octene copolymer (POE) and ethylene-octene block copolymer (OBC).

4. The thermoplastic vulcanizate material according to any one of claims 1 to 3, wherein: The weight average molecular weight of the styrene block copolymer is 50,000 to 300,000, preferably 50,000 to 100,000; the content of styrene is 20wt% to 50wt%, preferably 25wt% to 40wt%.

5. The thermoplastic vulcanizate material according to any one of claims 1 to 4, wherein: The styrene block copolymer is at least one selected from styrene / ethylene-butylene / styrene block copolymer (SEBS) and styrene / butadiene / styrene block copolymer (SBS).

6. The thermoplastic vulcanizate according to any one of claims 1 to 5, wherein: The cross-linking agent is at least one selected from di-tert-butyl peroxide, 2,5-dimethyl-2,5-bis(tert-butyl peroxide)hexane, 1,4-di-tert-butyl peroxyisopropylbenzene and diisopropylbenzene peroxide; Preferably, the crosslinking aid is at least one selected from triallyl isocyanurate, trimethylolpropane triacrylate and trimethylolpropane trimethacrylate; Preferably, the antioxidant is at least one selected from hindered phenol antioxidants, phosphite antioxidants and thioester antioxidants, preferably hindered phenol antioxidants and phosphite antioxidants; more preferably, the antioxidant is at least one selected from antioxidant 1010, antioxidant 245, antioxidant 168 and antioxidant 626.

7. The thermoplastic vulcanizate according to any one of claims 1 to 6, wherein: The thermoplastic vulcanizate material was molded into a 8 mm thick plate using a tablet press and cut into a cylinder with a diameter of 16 mm. The wear loss was then measured using a roller abrasion machine according to the GB / T 9867-2008 method and was 170 mm. 3 the following; Preferably, the thermoplastic vulcanizate material is pressed into a 2 mm thick sheet by a sheet press and cut into standard tensile specimens, and then placed in a test room for 24 hours, and tested using an Instron 5965 testing machine according to the GB / T 528-2009 method to obtain a tensile strength of more than 18 MPa; and a 300% elongation strength of more than 5.7 MPa.

8. A method for preparing a thermoplastic vulcanizate composition, comprising the following steps: (1) blending a styrene block copolymer, a polyolefin elastomer and an antioxidant, and then melt-blending and extruding the mixture through a twin-screw extruder, and granulating the mixture to obtain a primary thermoplastic elastomer material; (2) The primary thermoplastic elastomer, the crosslinking agent, and the crosslinking aid are blended, and then dynamically vulcanized and extruded through a twin-screw extruder to obtain a thermoplastic vulcanizate material.

9. The method for preparing a thermoplastic vulcanizate composition according to claim 8, wherein: The conditions for melt blending in step (1) are: extrusion temperature of 180-220° C.; extruder speed of 200-300 r / min; Preferably, the conditions for melt blending in step (2) are: extrusion temperature of 180 to 220° C.; and extruder speed of 60 to 150 r / min.

10. An article prepared from the thermoplastic vulcanizate composition according to any one of claims 1 to 7.